Faktor-faktor yang Mempengaruhi Kerusakan Arsip di Kantor Perpustakaan Arsip dan Dokumentasi Kota Bukittinggi - Saputra, Rio Agus; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper discusses the factors that affect the damage in the office archive libraries, archives and documentation of Bukittinggi. The purpose of this paper is: (1) Describe the intern factors affecting archives damage in Office Library, Archives and Documentation of Bukittinggi, (2) Describe the extern factors that influence damage records in the Office of Libraries, Archives and Documentation of Bukittinggi. From the results of this study concluded: (1) intern factor is the destructive factor derived from the archives. Factors damaging is the archive of the paper and the ink paper and ink as an object that can be easily damaged. For avoidance of anything like this, at the time of filing in paper and ink for choose a good quality that is not easily damaged archives and in doing maintenance, do so in accordance with the terms of the world of archives, (2) factor is a factor extern archives from destroyer from outside. Factors damaging records from outside is the temperature and humidity, as well as the use of dust and mishandling. This is caused by a lack of understanding of archivists in the process of maintenance records so that the archive was damaged and difficult to use anymore. In order for archive to be managed properly filing officer should provide equipment maintenance and managing archives in accordance with archival purposes. Keywords: maintenance records; factors affecting archives